Analysis of the complex influence of agrotechnological techniques on the switchgrass yield in the condition of the Central Forest-Steppe of Ukraine - Кулик, М. І. (Scientific Progress & Innovations, 2018)
Alternative resource of energy crops (including switchgrass) involvement to fuel and energy complex of Ukraine is a critical problem at present. Energy crops’ sowings management increases yield and oil equivalent output within the certain area of energy crop plot of land. That is why determination of the most influencing agrotechnological techniques (for cultivation technology elements improvement) over switchgrass yield is an important issue and requires a more complicated study. Research purpose is to determine switchgrass yield depending upon complex application of the cultivation technology elements. The agricultural experimental methods as well as proper theoretical and practical recommendations of switchgrass cultivation given by Wolter Elbersen, M. V. Roik, V. L. Kurylo and other scientists have been used in order to lay out the experiment and perform multiple-factor researches in the Forest-Steppe area. Obtained research results have been processed by application of Statistics computer programs. Change of switchgrass yield depending upon schemes of pre-sowing soil tillage has been observed. Switchgrass yield varied according to years in the range from 2.4 to 14.7 tons per hectare (1 cultivation), from 7.4 to 14.6 tons per hectare (2 cultivations), from 7.7 to 15.0 tons per hectare (2 cultivations and rolling) with general autumn soil tillage. Substantially higher indices have been provided on the options with semi-steam soil tillage, change of yield on the options according to the years was: option 1 – from 5.8 tо 14.4 tons per hectare, option 2 – from 10.8 to 14.7 tons per hectare and option 3 – from 12.3 to 15.5 tons per hectare. Dynamic of switchgrass yield growth applying nitrogen additional fertilizing and increasing the area of plant nutrition with optimal sowing term has been fixing within the experiment years. The best option was the option of switchgrass cultivation with row-spacing of 45 cm and application of spring additional fertilizing with dosing of 45 kg/ha. Applying less or bigger nitrogen dosing does not cause considerable yield increase, but even lessens this index except option with row-spacing of 15 cm and nitrogen application of 60 kg per hectare. It can be explained by plant competition for nutrients while growing them on narrow row-spacings and needs in higher nitrogen dosing. Although, there was not huge difference between application of N45 and N60 on the options with wider row-spacing of 60 cm. The maximum productivity the switchgrass depending on the sowing time was 3.0 million seeds on hectares. It is determined that the decrease, and an increase in this indicator leads to a decrease in crop productivity. Substantial influence of spring agrotechnological techniques performed before crop sowing process on the background of general and semi-steam soil tillage in autumn has been discovered on the basis of multivariate connection between the experiment options and yield of switchgrass dry biomass. Also, it has been established that the method of soil tillage as well as nitrogen additional fertilizing in spring had more significant influence on switchgrass yield.